Pneumococcal Forssman antigen: enrichment in mesosomal membranes and specific binding to the autolytic enzyme of Streptococcus pneumoniae. - Horne, D (1985)
The choline-containing pneumococcal membrane teichoic acid (Forssman antigen) can be isolated with the membrane fractions of the bacteria. The small vesicle (mesosomal) fraction generated during the formation of protoplasts seems to be highly enriched in this material. Forssman antigen was identified in cell fractions on the basis of (i) radioactive choline label, (ii) autolysin-inhibitory activity, and (iii) the sedimentation profile in sucrose density gradients with and without detergent. A membrane teichoic acid could also be isolated from pneumococci grown in medium in which choline was replaced by ethanolamine as the nutritionally required amino alcohol. This material contained radioactive ethanolamine label and behaved similarly to the choline-containing membrane teichoic acid during centrifugation in detergent-containing and detergent-free density gradients. On the other hand, the material had only low autolysin-inhibitory activity. Binding of pure pneumococcal autolysin to micelles of purified Forssman antigen could be demonstrated by mixing these components in vitro and analyzing them by sucrose density gradients and by agarose chromatography. No binding could be observed between the pneumococcal enzyme and the micellar forms of either cardiolipin or polyglycerophosphate-type lipoteichoic acid isolated from Streptococcus lactis.